2014
DOI: 10.1371/journal.pone.0102615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leucine Supplementation and Serum Withdrawal on Branched-Chain Amino Acid Pathway Gene and Protein Expression in Mouse Adipocytes

Abstract: The essential branched-chain amino acids (BCAA), leucine, valine and isoleucine, are traditionally associated with skeletal muscle growth and maintenance, energy production, and generation of neurotransmitter and gluconeogenic precursors. Recent evidence from human and animal model studies has established an additional link between BCAA levels and obesity. However, details of the mechanism of regulation of BCAA metabolism during adipogenesis are largely unknown. We interrogated whether the expression of genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Our results showed that BCAT2 could promote the differentiation of ovine preadipocytes, which was supported by previous research on mice. In the present study, BCAT2 exhibits a low expression level at the early stage and a high level at the late stage of differentiation, the BCAT2 expression is in accordance with the result of experiments in 3T3‐L1 preadipocytes (Estrada‐Alcalde et al., ; Kitsy et al., ). Lower BCAT2 expression at an early differentiation stage can be explained as possibly preserving BCAAs for later protein synthesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that BCAT2 could promote the differentiation of ovine preadipocytes, which was supported by previous research on mice. In the present study, BCAT2 exhibits a low expression level at the early stage and a high level at the late stage of differentiation, the BCAT2 expression is in accordance with the result of experiments in 3T3‐L1 preadipocytes (Estrada‐Alcalde et al., ; Kitsy et al., ). Lower BCAT2 expression at an early differentiation stage can be explained as possibly preserving BCAAs for later protein synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…Some research displayed that BCAT2 can promote the differentiation of 3T3‐L1 preadipocytes. BCAT2 is the upstream gene of BCKDHA and BCKDHB , and may regulate the expression of them during preadipocyte differentiation (Kitsy et al., ). The sequences of the three genes are known and have been cloned (Lu, Xie, Jia, & Jia, ).…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al found that a diet deficient in amino acids used for a period of 7 days quickly reduces abdominal fat mass in mice [17]. Recent scientific evidence from studies conducted on animals and humans have reported a link between levels of branchedchain essential amino acids and obesity [18]. Moreover, recent research suggests that leucine is involved in systemic cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The catabolism of BCAAs proceeds through transamination to the respective 2-oxo acids, followed by an intramitochondrial oxidative decarboxylation catalysed by the branched-chain 2-oxo acid dehydrogenase. It is not surprising, therefore, that during adipogenesis, when mitochondrial mass is elevated, leucine catabolism and the expression of enzymes involved in BCAA catabolism increased dramatically (Frerman et al 1983;Kitsy et al 2014). Furthermore, mice lacking the mitochondrial branched-chain aminotransferase enzyme at the whole-body level exhibited reduced adiposity and enhanced energy expenditure despite higher food intake and increased circulating levels of BCAAs (She et al 2007).…”
Section: Fatty Acid Esterification and Glyceroneogenesismentioning
confidence: 99%
“…; Kitsy et al . ). Furthermore, mice lacking the mitochondrial branched‐chain aminotransferase enzyme at the whole‐body level exhibited reduced adiposity and enhanced energy expenditure despite higher food intake and increased circulating levels of BCAAs (She et al .…”
Section: Introductionmentioning
confidence: 97%